Impact of non-pharmacological interventions on the first wave of COVID-19 in Portugal 2020 - Dinis B. Loyens; Constantino Caetano; Carlos Matias-Dias (Heliyon)
Introduction: The COVID-19 pandemic caused over 7 million global deaths. Without vaccines during the first wave, governments implemented nonpharmacological interventions (NPIs) such as lockdowns, school closures, and travel restrictions. This study quantifies the impact of NPIs on COVID-19 transmission in Portugal between 24th February and 1st May. Methods: A compartmental SEIR (Susceptible, Exposed, Infectious, Removed) model was employed to simulate the first COVID-19 wave in Portugal, using a Bayesian approach and symptom-onset incidence data. The effect of the lockdown, which began on March 22, 2020, on the effective reproductive number, Rt was measured. A counterfactual scenario was created to ascertain the number of cases prevented by the NPIs during the first 15 days after the implementation of NPI. Results: The lockdown reduced overall transmission by 68·6 % (95%Credible Interval (95%CrI): 59·2 %; 77·5 %), almost immediately. This corresponds to a reduction in the effective reproductive number from 2·56 (95%CrI: 2·08; 3·40) to 0·80 (95%CrI: 0·76; 0·84). The counterfactual scenario estimated that the lockdown prevented 118052 (95%CrI: 99464; 145605) cases between 24th February and 6th April. Discussion: The lockdown significantly reduced COVID-19 transmission in Portugal, bringing Rt below 1, meaning each person infected fewer than one individual. While costly, lockdowns effectively control disease spread in the absence of vaccines. Conclusion: Our findings suggest NPIs curbed epidemic transmission, reducing Rt below 1 and easing hospital loads and deaths. This research will help inform future pandemic decision-making and infectious disease modeling worldwide.